2004
DOI: 10.1073/pnas.0407550101
|View full text |Cite
|
Sign up to set email alerts
|

Impaired adrenal stress response in Toll-like receptor 2-deficient mice

Abstract: Septicemia is one of the major health concerns worldwide, and rapid activation of adrenal steroid release is a key event in the organism's first line of defense during this form of severe illness. The family of Toll-like receptors (TLRs) is critical in the early immune response upon bacterial infection, and TLR polymorphisms are frequent in humans. Here, we demonstrate that TLR-2 deficiency in mice is associated with reduced plasma corticosterone levels and marked cellular alterations in adrenocortical tissue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 42 publications
(39 reference statements)
5
61
1
1
Order By: Relevance
“…TLR2 and TLR4 in liver (Tsujimoto et al, 2005) or TLR2, TLR4 and TLR9 in peripheral blood (Brandl et al, 2005). This finding is in line with our previous results showing an upregulation of TLR2 and TLR4 in the adrenal glands of mice after injection of lipotechonic acid and LPS (Bornstein et al, 2004b;Zacharowski et al, 2006). In order to see whether an increased expression of TLRs in adrenocortical cells may impact adrenal steroidogenesis, we have stably transfected NCI-H295R cell with expression plasmid encoding either for TLR2 or TLR4-CD14 and tested basal and AII or FSK-stimulated hormone synthesis in these transfected cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…TLR2 and TLR4 in liver (Tsujimoto et al, 2005) or TLR2, TLR4 and TLR9 in peripheral blood (Brandl et al, 2005). This finding is in line with our previous results showing an upregulation of TLR2 and TLR4 in the adrenal glands of mice after injection of lipotechonic acid and LPS (Bornstein et al, 2004b;Zacharowski et al, 2006). In order to see whether an increased expression of TLRs in adrenocortical cells may impact adrenal steroidogenesis, we have stably transfected NCI-H295R cell with expression plasmid encoding either for TLR2 or TLR4-CD14 and tested basal and AII or FSK-stimulated hormone synthesis in these transfected cells.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously shown expression of several TLRs in mouse and human adrenal glands and in primary cultures of adrenocortical cells (Bornstein et al, 2004a;Kanczkowski et al, 2009). Moreover, we found that TLR2, TLR4 or TLR9 ligands when administered to mice induce a strong systemic and local inflammation of adrenal gland with upregulation of the major proinflammatory cytokines such as IL-1 , IL-6 and TNF- (Bornstein et al 2004b) Interestingly, in the latter study we have found un upregulation of both TLR2 and TLR4 expression in the adrenal glands from mice that received a single dose of LPS or lipoteichonic acid (Bornstein et al, 2004b). However, we also found that TLR2 and TLR4 deficiency results in a dysregulation of adrenal glucocorticoid production and increased mortality of TLR2 and TLR4 deficient mice.…”
Section: Introductionmentioning
confidence: 81%
“…The former feature is well documented, at least in the rat, and suggests a higher responsiveness of adrenal cortex to ACTH in females (see Atkinson and Waddell, 1997 and references therein;Spinedi et al, 1997). Supporting this hypothesis, TLR2À/À mutant mice that bear an impaired adrenal gland display higher ACTH but decreased corticosterone basal levels (Bornstein et al, 2004). The latter aspect can also be explained by this mechanism, where less ACTH is required to achieve a given corticosterone response.…”
Section: Discussionmentioning
confidence: 54%
“…Likewise, IL-1 and its receptor are also produced in the adrenal glands and contribute to steroidogenesis at least partly by regulating prostaglandin pathways [47]. Toll-like receptors (TLR), mainly TLR2 and TLR4, are expressed in the adrenal glands and play a critical role in the local immune-endocrine crosstalk in LPS-challenged rodents [48,49]. Further experiments using genetically manipulated mice suggest that immune cells and not steroid-producing cells are key regulators of the immune-endocrine local interaction [49].…”
Section: Cytokine-induced Activation Of the Hpa Axismentioning
confidence: 99%